PEMANFAATAN HUTAN KOTA DI WILAYAH JAKARTA TIMUR SEBAGAI KAWASAN REKREASI MASYARAKAT KOTA - Nike Dyah Permata; . Syartinilia; Aris Munandar (http://arl.faperta.ipb.ac.id/, 2018)
Urban forests have benefits for urban recreational activities for dwellers and also the identity of a city. East Jakarta is one of the areas in DKI Jakarta that has the largest number of urban forests currently. Urban forest has not been utilized optimally by the dwellers. For recreation activities, urban forest utilization for recreation activities become an interesting to observe. Therefore, the objective of this study was to analyzed urban forests utilization by the dwellers,especially in East Jakarta. Observation was done through interview and then was analyzed using linier regression. Urban forests coverage area were determined through buffer analysis using the level of urban forest accessibility by walk. The results shown that 85% urban forests was visited by dwellers came from inside urban forest coverage area. Recreational activities recorded while observed in the urban forest were exercising, sightseeing, picnic, camping, etc. The number of object in each urban forest was positively correlated with the high proportion of visitor from outside the urban forest coverage area.